Analisis Puisi “Demokrasi” Karya Agam Wispi melalui Pendekatan Semiotika (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This article discusses the poem "Democracy" by Agam Wispi through a semiotic approach. According to Tinarbuko (2008), semiotics is the study of signs in order to find out how these signs function and produce a meaning. Meanwhile, according to Christomy and Yuwono (2004), argue that semiotics is the study of signs (signs), sign functions, and sign production. In semiotics there is a signifier (signifier) ​​which is a sign that can be seen by the eye, visible form / physical form while the signified (signified) is the meaning contained in the message that has the concept, function, and value contained in the sign. So the purpose of this study is to find out the signs of meaning in the poem "Democracy" through the method. In this study using semiotic analysis. Semiotic analysis is a qualitative data analysis technique that aims to find or analyze symbols or signs in a text systematically. And the conclusion in this study is that based on the analysis above, it can be concluded that the poem "Democracy" by Agam Wispi strongly ties its meaning to Indonesian political life. In discussing the poem, it tells about the people's struggle to burn and replace the rights they should have received for the hard work and sacrifices that have been made.